Benefit Incidence Analysis of Uninhatitable Houses Rehabilitation Program in Indonesia - Fakhrun Nisa , Amalia; Setyadharma, Andryan (KnE Social Sciences, 2020)
The Government of Indonesia has launched new social assistance program named the Uninhabitable Houses Rehabilitation Program (in Indonesian: Program Rumah Tidak Layak Huni). Uninhabitable Houses Rehabilitation program is a social assistance program that aims to restore social functioning and improve the quality of poor housing that is initially uninhabitable to be habitable. This study aims to evaluate the achievement of the Uninhabitable Houses Rehabilitation Program in Grobogan Regency, Central Java Province, Indonesia. Grobogan Regency has the highest number of uninhabitable houses compared to another regencies and cities in Central Java Province. The method used in this study is Benefit Incidence Analysis (BIA). This model shows the distribution of public expenditure made by the government into different community groups based on the level of income, so that it is expected to explain the progression of the Uninhabitable Houses Rehabilitation program given by the government to the residents of Grobogan Regency. The results of this study indicate that the Uninhabitable Houses Rehabilitation program in Grobogan Regency is a progressive policy, because the benefits received by the poor are more than 10%, i.e. 12,12%.